USULAN STRATEGI PEMASARAN PADA PRODUK TAS RANSEL DI UKM UD.RISSLIN DENGAN METODE SWOT DAN QSPM - muhammad syaifudin; Said Salim Dahda; Elly Ismiyah (Universitas Muhammadiyah Gresik, 2021)
The development of business in the era of globalization has increased, the increasing competition between companies is getting higher, causing companies to have to develop marketing strategies to attract consumer interest and maintain continuity in the face of competition. This study uses data processing methods in the form of Strengths, Weaknesses, Opportunities and Threats (SWOT) and Quantitative Strategic Planning Matrix (QSPM). SWOT is used to measure internal and external conditions, in the form of strengths and weaknesses made in the IFE matrix and opportunities and threats created in the EFE matrix. The first stage is weighting, rating and calculating the weighted value of the IFE and EFE matrices, then formulating a marketing strategy with an Internal External and SWOT matrix, and the last stage is the stage of choosing alternative strategies using the QSPM method which is a method for determining alternative strategies objectively based on key success factors. previously identified internal and external. The input stage is to make IFE and EFE matrices. The matching stage uses a SWOT matrix and the decision stage uses QSPM. The results showed that alternative strategies were obtained, namely replacing materials with relatively cheaper materials with almost the same quality to compete with products from other industries(S9)